Resolving Inherent Statutory Fault Lines in the Combat of Corruption and Maleficence in the Local Government Sector through Improved Collaboration with Law Enforcement Agencies - Karsten, Andreas; Birch, Gary (Journal of Anti-Corruption Law, 2025)
Unchecked corruption in government has the potential to severely undermine real service delivery in the public sector. In context of public expenditure, the Constitution mandates organs of state in the national, provincial and local spheres of government to ensure the execution of transparent and fair processes in public procurement and also execute responsible management of public finances. Equally, municipalities must account to its constituents or local communities in relation to expenditure of public funds. Unfortunately, municipalities often have poor track records in financial management and Municipal Councillors and senior officials are frequently linked to or implicated in financial irregularities. Specific to allegations of maladministration, fraud, corruption or any other serious malpractice in municipalities, section 106 of the Local Government: Municipal Systems Act (32 of 2000) (the “Systems Act”) empowers the MEC responsible for local government, in the different provinces, to request information or to designate an investigator(s) if he or she has reason to believe that “maladministration fraud, corruption or any other serious malpractice has occurred or is occurring in a municipality”. However, said allegations are often the subject of a wide range of alleged misconduct and criminalities which require multiple entities to actively investigate allegations of corruption in municipalities. Investigation of such allegations are often hindered by fragmentation of mandates and legislation dealing with the investigation of corruption and maleficence. This is because the investigation of these offences is often mandated to different investigative bodies/actors each with their own powers and limitations. The impact of investigations of allegations of malfeasance at municipalities is further complicated by the fact that investigative bodies/actors have different mandates and consequences following from adverse findings. This issue arises from the current fragmented legislative approach in relation to the same investigation and related events. It follows that these statutory fault lines created could therefore, if not properly managed, cause specific misconduct or criminal acts to pass unnoticed or not be properly investigated. Statutory gaps and overlapping mandates created by segregated legislation further stands to cause either costly duplications of investigations or, conversely, a limited mandate that prevents relevant entities/agencies from fully addressing the full extent of the wrongdoing. It is with the shortcomings and current segregated nature of investigation of allegations related to municipalities in mind, that this research paper seeks to examine the various codified statutes from a South African law perspective that mandates the investigation of corruption in local government. It is suggested that a holistic statutory review of the various statutes that mandates the investigation of allegations of maladministration, fraud, corruption or any other serious malpractice would allow for a better understanding of the exact ambit of the legislative framework in this regard. The framework developed, following from the above, will equally clarify and create a better understanding of each legislated actor’s mandate and produce a cooperative model to be used for better collaboration between legislated actors like government departments, investigation bodies and law enforcement agencies when investigating allegations related to municipalities. The framework or model will also enable a more efficient, enhanced and cooperative approach amongst the various investigation bodies/actors when investigating corruption in municipalities. It follows that a widely publicised collaborative approach to investigating malpractice and offenses in municipalities is, therefore, the most effective way to eradicate financial irregularities, ensure sound financial management and sustainable good governance practices.